Occupational and Environmental Noise Exposure and Extra‐Auditory Effects on Humans: A Systematic Literature Review - Lee, Yongho; Lee, Seunghyun; Lee, Wanhyung (Geohealth, 2023)
Noise is a common harmful factor in our work and the environment. Most studies have investigated the auditory effects of noise exposure; however, few studies have focused on the extra‐auditory effects of exposure to occupational or environmental noise. This study aimed to systematically review published studies on the extra‐auditory effects of noise exposure. We reviewed literature from PubMed and Google Scholar databases up to July 2022, using the Patient, Intervention, Comparison, and Outcome criteria and Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines to identify studies that reported extra‐auditory effects of occupational or environmental noise exposure. Studies were evaluated utilizing validated reporting tools (CONSORT, STROBE) appropriate to study design. A total of 263 articles were identified, of which 36 were finally selected and reviewed. Upon conducting a review of the articles, exposure to noise can elicit a variety of extra‐auditory effects on humans. These effects include circulatory effects linked to higher risk of cardiovascular disease and decreased endothelial function, nervous system effects correlated with sleep disturbance, cognitive impairment, and mental health problems, immunological and endocrinal effects connected to increased physiological stress response and metabolic disorders, oncological and respiratory effects associated with an elevated risk of acoustic neuroma and respiratory disorders, gastrointestinal effects linked to an increased risk of gastric or duodenal ulcer, and obstetric effects connected to the risk of preterm birth. Our review suggests that there are numerous extra‐auditory effects of noise exposure on human, and further investigations are needed to fully understand these effects. Plain Language Summary Noise is a common harmful factor in both our work and environment. While many studies have focused on the auditory effects of noise exposure, few have examined the extra‐auditory effects of exposure to occupational or environmental noise. This study aimed to systematically review published studies on the extra‐auditory effects of noise exposure. We searched the PubMed and Google Scholar databases, following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, to identify studies that reported extra‐auditory effects of occupational or environmental noise exposure. We found 262 articles, of which 36 were ultimately selected. These studies have reported various health effects associated with noise exposure, such as circulatory, respiratory, immunological, gastrointestinal, and oncologic effects. The findings suggest that there are various extra‐auditory effects of noise exposure on human health, and further investigations are necessary. Key Points Noise is common harmful factor in our work and environment Few studies have focused on the extra‐auditory effects of noise Various extra‐auditory health effects of noise exposure have been reported, such as circulatory, respiratory, immunological, gastrointestinal, and oncologic effects